Central courts in early modern Europe and the Americas - Godfrey, Andrew Mark; Rhee, C. H. van (Comparative studies in Continental and Anglo-American legal history, 2020)
Intro -- Preface -- Table of Contents -- A. M. Godfrey / C. H. van Rhee: Introduction -- 1. Central courts -- 2. Jurisdiction -- (a) Defining central court jurisdiction -- (b) Jurisdictional change conditioned by wider political context -- (c) Shaping of jurisdiction through innovations in procedure and remedies -- (d) Importance of appeals in developing supreme jurisdiction -- (e) General or supplementary models of central jurisdiction -- (f) Contesting and declining jurisdiction -- (g) Jurisdictional complexity and institutional competition -- (h) Limits on jurisdiction -- (j) Central jurisdiction and unlocking the procedural rigidity of medieval legal process -- 3. Central courts, privy councils and parliaments -- (a) Relieving the burden of judicial work on royal councils -- (b) Privy councils in relation to the jurisdiction of ordinary courts -- (c) The indeterminacy of residual jurisdiction: blurred division between executive and judicial bodies -- (d) Lack of unified ordinary jurisdiction balanced by development of extraordinary jurisdiction -- (e) Personal intervention by the monarch and the exercise of grace -- (f) Privy councils and jurisdictional conflict -- Conclusion -- Bibliography -- K. Salonen: The Sacra Romana Rota -- 1. What was the medieval Sacra Romana Rota? -- 2. The birth and development of the Sacra Romana Rota -- 3. Jurisdiction of the Sacra Romana Rota -- 4. The role of the Rota in the papal administration -- Conclusions -- Bibliography -- N. G. Jones: The English Court of Chancery -- Introduction -- (a) Central court jurisdiction in England, 1200-1700 -- (b) The location and staffing of the Court of Chancery -- 1. The development of the Court of Chancery -- (a) The general relationship between the courts and royal exercise of judicial authority -- (b) The Court of Chancery as a new institution.